FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU AUDIT DISFUNGSIONAL - , EUNIKE HEDRIANI PARDEDE; , Dewi Fatmawati, S.E., M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this paper is to investigate the relationship between the effect of time budget pressure, external locus of control, turnover intentions and self-rated employee performance to dysfunctional audit behavior. In addition, we also examine the moderating effect of quality control and review procedures of the relationship between several independent variables with dysfunctional audit behavior. This research will be conducted as quantitative research that used survey method by questionnaire. We used multiple linear regression analysis for the first to the fourth hypothesis and Moderated Regression Analysis (MRA) for the fifth hypothesis. The results show that time budget pressure and external locus of control were positively associated with the dysfunctional audit behavior. Turnover intentions and self-rated employee performance have a negative effect on dysfunctional audit behavior. The quality control and review procedures may moderate the relationship of time budget pressure on dysfunctional audit behavior.